2018
DOI: 10.1002/2017gl076110
|View full text |Cite
|
Sign up to set email alerts
|

Pore Pressure Pulse Drove the 2012 Emilia (Italy) Series of Earthquakes

Abstract: The 2012 Emilia earthquakes sequence is the first debated case in Italy of destructive event possibly induced by anthropic activity. During this sequence, two main earthquakes occurred separated by 9 days on contiguous thrust faults. Scientific commissions engaged by the Italian government reported complementary scenarios on the potential trigger mechanism ascribable to exploitation of a nearby oil field. In this study, we combine a refined geodetic source model constrained by precise aftershock locations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…On the other hand, we observe transient high V p / V s anomalies in the deeper part of the MLGf footwall (Figure ) that we interpreted as overpressurized fluids. This might suggest a process similar to that observed during the 1997 Colfiorito (Chiarabba et al, ; Miller et al, ), the 2009 L'Aquila (Malagnini et al, ) and the 2012 Emilia sequences (Pezzo et al, ), where the partial activation of the segment was interpreted as due to pore pressure diffusion. In this view, the transient pore pressure pulse for the 2009 large shock on the MLGf can be invoked as a viable triggering mechanism for multiple ruptures, as recently described by Walters et al () either for long clustered super seismic sequences (Chiarabba et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, we observe transient high V p / V s anomalies in the deeper part of the MLGf footwall (Figure ) that we interpreted as overpressurized fluids. This might suggest a process similar to that observed during the 1997 Colfiorito (Chiarabba et al, ; Miller et al, ), the 2009 L'Aquila (Malagnini et al, ) and the 2012 Emilia sequences (Pezzo et al, ), where the partial activation of the segment was interpreted as due to pore pressure diffusion. In this view, the transient pore pressure pulse for the 2009 large shock on the MLGf can be invoked as a viable triggering mechanism for multiple ruptures, as recently described by Walters et al () either for long clustered super seismic sequences (Chiarabba et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…In the depth range 6-9 km, where most of the aftershocks occurred, they can reach several MPa magnitude, as basically due to the coseismic pressure change history Δp c t , which persists on a one-year time scale ( Figure 5(g)). In the same depth range, Pezzo et al [50] find V P /V S variations possibly related to pore-pressure changes. We cannot exclude that the slow fluid flow occurring at hypocentral depth could have played an active role in carrying on the Emilia-Romagna seismic sequence, but given the small postseismic porepressure and CFF changes here obtained, we think that the triggering of the Mirandola fault is more due to coseismic pore-pressure and CFF changes than to fluid migration.…”
Section: Discussionmentioning
confidence: 91%
“…In this view, the outermost ramp of the northern Apennines belt in the studied marine region may be a potential seismic source, although other more internal thrust faults could be potentially seismic as well. Considering the detachment depth (Petricca et al, 2019), we cannot exclude, along these structures, seismic events, similar to the Mw 6.0 and Mw 5.8 2012 Emilia earthquakes (e.g., Govoni et al, 2014; Pezzo et al, 2013, 2018) and to those reported in the historical seismic catalog (e.g., Camassi et al, 1991 and references therein, Molin et al, 2008), even though seismic reflection profiles in our and previous studies (Di Bucci & Mazzoli, 2002 and references therein) show no evidence of active tectonic deformations. This lack of evidences in the recent Quaternary deposits could be related to the effect of the large increase of sediment supply in the foredeep during the Quaternary eustatic low stand, which eventually produced a smaller apparent fault throw or masked the internal tectonic deformation (Scrocca et al, 2007).…”
Section: Discussionmentioning
confidence: 99%